Dahuang Zhechong Pills Suppress Silicosis Fibrosis Progression via p38 MAPK/TGF-β1/Smad Pathway In Vitro. (2nd April 2021) - Wu, Li-Juan; He, Xiao-Yan; Wang, Wen-Xiang; Liang, Jie; Zhang, Yu-Die; Liang, Jing-Tao; Chen, Da-Yi
Abstract : Background . Dahuang Zhechong pills (DHZCP) is a classic Chinese medicinal prescription in "Treatise on Cold Pathogenic and Miscellaneous Diseases (Shanghan Zabing Lun), " and it has the function of tonifying blood, nourishing Yin, and removing blood stasis. Previous studies have shown that DHZCP could alleviate SiO2 induced pulmonary fibrosis in mice. This study aims to further explore the preventive and therapeutic effects of DHZCP against silicosis fibrosis and the underlying mechanisms in vitro . Methods . We used the experimental model of SiO2 -induced MH-S cells to evaluate the therapeutic potential of DHZCP. MH-S cells induced by SiO2 were intervened with the drug-containing serum of DHZCP, and the effects of drug-containing serum of DHZCP on the MH-S cells were detected by CCK8, ELISA, flow cytometry, western blot, and immunofluorescence. Results . DHZCP improved cell viability by reducing apoptosis. It also decreased the levels of TNF- α, IL-1 β, IL-6 in the supernatant of MH-S cells induced by SiO2, inhibited the expression of p38 MAPK, blocked the activation of NF- κ B, and controlled the upstream inflammatory response by multiple targeting. Concomitantly, we observed upregulation of Smad7 and a marked decline in TGF- β 1, α -SMA, Smad2, Smad3 expression in MH-S cells treated with DHZCP. Conclusion . To sum up, we conclude that DHZCP protects against SiO2 -induced silicosis by reducing the persistent irritation of inflammation, regulating the p38 MAPK/TGF- β 1/Smad pathway.